SOCIAL CAPITAL AND QUALITY OF EDUCATION IN FAJAR UNIVERSITY MAKASSAR - Sri Adrianti Muin (Salewangang Institut Publishing, 2018)
This study aims to determine social capital in quality of education at Fajar University Makassar. This research uses descriptive qualitative method, with research subject that is element of leadership, lecturer, staff and student. Sampling technique is purposive sampling method. Technique of collecting data by observation, interview and documentation. Data analysis by reducing data, presenting data and drawing conclusions. Test data validity using source and method triangulation. The elements of social capital studied are 1) the network consists of a solid relationship, cooperation and the use of social media as a means of liaison. 2) beliefs consisting of honesty, openness, and public interest, 3) institutions ie religious values, discipline, neatness and lecture contracts